Adolescent Risk-Taking and Future Roles: The Relationship between Delinquency, Substance Use, and Self-Efficacy - Luo, Sha; Blair, Sampson Lee (International Journal of Criminology and Sociology, 2026)
Adolescents often engage in a variety of risk-taking behaviors, such as substance use and delinquency, and these behaviors can result in a multitude of possible consequences. In particular, adolescents’ perception of their capacity to function in specific adult roles, self-efficacy, is developed during the adolescent years. This study uses a nationally representative sample of high school seniors to examine how risk-taking behaviors may influence various forms of self-efficacy, and also how the social contexts of adolescents may impact self-efficacy, as well. Adolescents are shown to maintain relatively high levels of self-efficacy, indicating confidence in their ability to perform in adult roles. Alcohol use and delinquent behaviors are both shown to be salient predictors of self-efficacy, and peer factors are also revealed to have meaningful associations with self-efficacy. The findings and implications of this study are discussed within the framework of ecological systems theory.